Viability amid systemic crisis: The CORER framework - Russo-Spena Tiziana; Mele Cristina; Kaartemo Valtteri; Caputo Francesco; Marzzullo Marialuisa (Emerald, 2022)
Purpose
The COVID-19 wave spread all over the global market, affecting all industries. This paper aims to develop the understanding of how service systems can enhance their viability when facing rapid systemic changes.
Design/methodology/approach
The authors use data from Reddit, and particularly the subreddit r/coronavirus, to identify posts that discuss the impact of coronavirus on business. The authors use an algorithm to scrape the data with business-related search terms and elaborate relevant posts.
Findings
The findings show key topics and related sentiments on the impact of COVID-19 on business. Service systems can enhance viability by identifying alternative paths for emerging opportunities (by being creative), seize opportunities offered by the changing environment (by being opportunistic), not compromise conditions for internal balance (by being resilient), focus attention on critical purposes (by being essential) and perform nonharmful actions (by being responsible).
Originality/value
This paper proposes a framework depicting five possible key enhancers of viability to face a systemic crisis. In brief, companies need to ensure that they are creative, opportunistic, resilient, essential and responsible.